Secondary traumatic stress among wives of war veterans - Stevanović, Aleksandra; Frančišković, Tanja; Kuterovac-Jagodić, Gordana (2013)
Previous studies have shown that some wives of war veterans with PTSD develop symptoms of secondary traumatic stress (STS). The aim of this study was to compare the level of present psychological symptoms and perceived quality of life between the wives of veterans with PTSD, without PTSD, and wives of non-veterans. Wives of veterans with PTSD (N = 50) were recruited through their partners and war veterans treated for combat related PTSD in Referent Center for Psychotrauma Rijeka, Croatia. Wives of veterans without PTSD (N = 50) and wives of non-veterans (N = 50) were recruited using the snowballing method. We administrated Sociodemographic questionnaire, Brief symptom inventory, Manchester Short Assessment of Quality of Life and Modified Questionnaire for Secondary Traumatization. Obtained results show that wives of veterans with PTSD have significantly higher level of STS symptoms than wives of veterans without PTSD, and higher level of psychological symptoms and lower perceived quality of life compared to other two groups. Level of STS symptoms is positively correlated with psychological symptoms and negatively with perceived quality of life. Main effect on STS symptoms has the wives' knowledge of partner's war traumatic event while the main effect on wives' psychological symptoms has the presence of PTSD in their husbands. In conclusion, when planning the future interventions for PTSD affected veterans, systemic approach should be considered not only to prevent secondary traumatic stress in partners of war veterans but also to enhance individual functioning of each partner and functioning as a couple.
Projekt MZOS
ENG